Cultural disgrace among tuberculosis patients in Sagar district of Madhya Pardesh in India - Saad, Talha; Tirkey, Abhay Shashin; Khan, Wahid (International Journal of Research in Medical Sciences, 2016)
Background: The overall objective of the research study was to gather new empirical evidence and develop further theoretical understanding of the mechanisms of stigma associated with TB and delay in seeking its treatment. Methods: This prospective study was carried out in the outpatient of Pulmonary Medicine at Bundelkhand Government Medical College, Sagar. The sample consisted of 300 tuberculosis patients. Between patients who consider TB a stigmatizing disease and patients who did not consider TB a stigmatizing disease distribution of patient delay was compared. Results: Of the total of 300 patients 79 (26.3%) considered TB a socially stigmatizing disease. Among them 43 (54.4%) were females and 36 (45.6%) males. Among patients in the age group 18-24 years, nine (50%) considered TB a socially stigmatizing disease compared to seven (12.3%) among patients in the age group 65-75 years. The average time interval from the appearance of first symptoms of tuberculosis until the first visit to a health care facility for those who consider TB a stigmatizing disease was 6.41 weeks and for those who did not consider it a stigmatizing disease the average time interval was 4.99 weeks. Conclusions: Most TB patients failed to recognize their symptoms as due to TB, because of the stigma attached to the disease in society. The way people treat those with TB, especially close contacts is also a source of worry to the patients. This may lead to delay in reporting to the hospital and consequently increase mortality from the disease. It may also make it difficult for the patients to comply with the long duration of TB treatment. Study results revealed high stigma-generating attitudes towards tuberculosis.